Exploring Factors Associated With Depressive Symptoms Among Patients With Chronic Pain: A Cross-Sectional Multicenter Study. Issue 1 (January 2022) - Al Shukaili, Mohamed; Al Alawi, Mohammed; Al Huseini, Salim; Al Shukaili, Ahmed; Al Muharrami, Maya; Al Abdali, Marwa; Al Harthi, Hiba; Al Saadi, AlKhatib; Al Balushi, Rasheeda; Al Kasbi, Fatma; Al-Fahdi, Amal; Panchatcharam, Sathiya Murthi; et al.
Abstract : Abstract: This cross-sectional study examined the factors associated with depression among people with chronic pain (PwCP) attending specialized pain clinics in Muscat, Oman. Two-hundred eighty-seven participants were recruited for the study, and univariate analyses were used to investigate the difference between individuals who scored above/below the cutoff points for depressive symptoms. A multiple regression analysis was used to detect the independent predictors. Twenty-six percent of participants scored above the cutoff point. Further analysis indicated that unstable family relationships pre-existing depressive symptoms (odds ratio [OR], 2.86; p = 0.044), a family history of depression (OR, 4.75; p = 0.019), severe pain (OR, 4.21; p < 0.006), having fibromyalgia (OR, 28.29; p = 0.005), and lumbago/truck (OR, 2.41; p = 0.039) were independent predictors of depressive symptoms. This study indicates that one in four patients with chronic pain also presents with depressive symptoms. However, the role of culture needs to be taken into consideration when interpreting these findings and when building on these data.